STRATEGI KOMUNIKASI PERSUASIF PERSONAL SELLING ANGGOTA PAYTREN DALAM MELAKUKAN NETWORK MARKETING DI PEKANBARU - Septiana, Nurul; Firdaus, Muhammad (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2018)
business is one of the newest business that currently growing up in Indonesia. This business works with selling the linceses of PayTren application itself. PayTren application is an application that allows users to perform online transactions. PayTren business began to enter and grow rapidly to Pekanbaru City since 2014. The system applied in this business is a network or network marketing system where the success of this business depends on the performance of each member in conducting persuasive communication in the form of an invitation to prospects or prospective members. This study aims to determine the persuasive communication strategy of personal selling members PayTren in doing Network Marketing in Pekanbaru City. This study uses a persuasive communication model by Applebaum and Anatol as a reference. The method used in this research is descriptive qualitative, data collection technique by doing observation, interview, and documentation. Research subjects are PayTren members in Pekanbaru City, The object of research is PayTren application, while documentation use done during writer run research in field. The results of this study indicate that the process of persuasive communication is done by psychodynamic strategy, sosiokultura strategy, and strategy of meaning construction. Persuasive Communication Principles that are applied in the persuasive communication process of PayTren members are the principles of selective exposure, the principle of audience participation, the principle of inoculation, and the principle of the magnitude of change. While the techniques of persuasive communication used are the yes-response technique, putting it 'up to you' technique, transfer technique, the technique say it with flowers, and techniques dont ask if ask which. Segmentation targeted by PayTren members is the society aged 15 to 50 years and preferably to the Muslims.Keywords: Persuasive Communication, Personal Selling, PaTren